Manajemen Strategik Dalam Pengembangan Rumah Sakit : Sebuah Tinjauan Literatur - Nerissa Arviana; Muhammad Joni Chandra; Yani Restiani Widjaja; Purwadhi Purwadhi (LPPM Universitas Buddhi Dharma, 2025)
This study aims to provide a systematic analysis of the role of strategic management in hospital development, with a focus on improving operational efficiency, competitiveness, and healthcare service quality. The research employs a qualitative method using a literature review approach, covering articles published between 2014 and 2024. The primary data sources consist of scientific articles from Scopus and Google Scholar databases, using the keywords